Blow-Up Solutions and Global Existence for Quasilinear Parabolic Problems with Robin Boundary Conditions - Juntang Ding (Abstract and Applied Analysis)
We study the blow-up and global solutions for a class of quasilinear parabolic problems with Robin boundary conditions. By constructing auxiliary functions and using maximum principles, the sufficient conditions for the existence of blow-up solution, an upper bound for the “blow-up time,” an upper estimate of the “blow-up rate,” the sufficient conditions for the existence of global solution, and an upper estimate of the global solution are specified.